2018
DOI: 10.1016/j.adolescence.2018.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Considering the negatively formed identity: Relationships between negative identity and problematic psychosocial beliefs

Abstract: Introduction: Developing a firm sense of identity is a critical developmental task in adolescence and emerging adulthood, but little or no empirical research exists regarding individuals who firmly form negative identities and psychosocial beliefs. This study examined the formation of negative identities in youth and its association with psychosocial beliefs in terms of variableoriented psychosocial facets (i.e., dichotomous beliefs, cynicism, and social distrust) and personoriented psychosocial profiles. Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(34 citation statements)
references
References 47 publications
1
32
0
1
Order By: Relevance
“…We used 2 items (Flanagan & Stout, 2010; see Hihara, Umemura, & Sugimura, 2019 for the Japanese version): “In general, most people can be trusted” and “most people are fair and do not seek to take advantage of you.” These items were rated on a 5-point Likert-type scale ranging from 1 ( strongly disagree ) to 5 ( strongly agree ). The internal consistency, estimated using a Spearman–Brown coefficient, was .84.…”
Section: Methodsmentioning
confidence: 99%
“…We used 2 items (Flanagan & Stout, 2010; see Hihara, Umemura, & Sugimura, 2019 for the Japanese version): “In general, most people can be trusted” and “most people are fair and do not seek to take advantage of you.” These items were rated on a 5-point Likert-type scale ranging from 1 ( strongly disagree ) to 5 ( strongly agree ). The internal consistency, estimated using a Spearman–Brown coefficient, was .84.…”
Section: Methodsmentioning
confidence: 99%
“…Positive and negative identity elements may, in turn, influence the identity exploration and commitment processes. Individuals holding identities with high levels of positive identity elements have a sense of trust in others/society (Hihara et al, 2019). Based on this sense of belonging, they may proactively engage in searching, revising, and implementing their commitments.…”
Section: Interplays Of Identity Exploration and Commitment Processes ...mentioning
confidence: 99%
“…Indeed, narrative research has revealed how individuals develop their identities by negotiating with sociocultural expectations (McLean et al, 2018). Several studies have examined positive and negative identity elements using identity-related short narratives (Hihara et al, 2021, 2019). In this procedure, participants express their identity elements to the open-ended question “Who am I?” using the language of their own culture.…”
Section: Identity Exploration and Commitment Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…La necesidad de esta adquisición de saberes y conocimientos hace que la necesidad de la escolarización sea obligatoria, así como de la formación superior, la cual cada vez más va dilatando el ingreso al mercado laboral de los sujetos, con lo cual la adolescencia emerge en este contexto político y económico particular. Tales prácticas y saberes que se reproducen en modelos actuales -como la psicología positiva-, vinculados a la causalidad, individualismo y a la "tiranía de la actitud positiva" (Prieto-Ursúa, 2006, p. 329), facilitan que los procesos de subjetivación se desarrollen desde la participación en la sociedad del rendimiento (Han, 2016). Un ejemplo son las denominadas estrategias de afrontamiento -como la resolución de problemas o el pensamiento positivo-propuestas por la Psicología Positiva, donde las investigaciones buscan incluso conocer las más adecuadas -referidas como activas-para que los adolescentes puedan alcanzar el bienestar y la autorregulación emocional (Pascual, Conejero, & Etxebarria, 2016).…”
Section: Adolescencia Y Bienestar Subjetivounclassified